Streamlined vessels for speedboats: Macro modifications of shark skin design applications - Mohd Danial, bin Ibrahim; S. N. A., Amran; Azham, bin Zulkharnain; Sunami, Yuta (American Institute of Physics Inc., 2018)
Functional properties of shark denticles have caught the attention of engineers and scientist today due to the hydrodynamic effects of its skin surface roughness. The skin of a fast swimming shark reveals riblet structures that help to reduce skin friction drag, shear stresses, making its movement to be more efficient and faster. Inspired by the structure of the shark skin denticles, our team has conducted a study on alternative on improving the hydrodynamic design of marine vessels by applying the simplified version of shark skin skin denticles on the surface hull of the vessels. Models used for this study are constructed and computational fluid dynamic (CFD) simulations are then carried out to predict the effectiveness of the hydrodynamic effects of the biomimetic shark skins on those models. Interestingly, the numerical calculated results obtained shows that the presence of biomimetic shark skin implemented on the vessels give improvements in the maximum speed as well as reducing the drag force experience by the vessels. The pattern of the wave generated post cruising area behind the vessels can also be observed to reduce the wakes and eddies. Theoretically, reduction of drag force provides a more efficient vessel with a better cruising speed. To further improve on this study, the authors are now actively arranging an experimental procedure in order to verify the numerical results obtained by CFD. The experimental test will be carried out using an 8 metre flow channel provided by University Malaysia Sarawak, Malaysia. © 2018 Author(s).